Focal vibrations enhance somatosensory facilitation in healthy subjects: A pilot study on Equistasi® and high-frequency oscillations - Cruciani, Alessandro; Lanzone, Jacopo; Musumeci, Gabriella; Di Lazzaro, Vincenzo; Marano, Massimo (Frontiers in Neurology, 2022)
Background Equistasi® is a vibrotactile device composed of nanotechnology fibers that converts temperature change into mechanical energy by self-producing a focal vibration. It is used in non-pharmacological rehabilitation in patients with movement disorders and multiple sclerosis sequelae. Nonetheless, the mechanism underlying such an improvement in motor functions is still poorly understood. Objectives We designed a small uncontrolled pilot trial to explore the effect of Equistasi® on the somatosensory pathway through the analysis of high-frequency oscillations (HFOs). Methods For all the included subjects, we recorded somatosensory-evoked potentials (SEPs) at the baseline (T0) and at 60 min after the application of Equistasi® (T1) on the seventh cervical vertebra level and at the forearm over each flexor carpi radialis, bilaterally. Then, we extracted the HFOs from the N20 signal and compared the HFO duration and area under the curve pre- and post-Equistasi® application. Results In a head-to-head comparison of T0 to T1 data, there was a statistically significant reduction in the total HFO area (p < 0.01), which was prominent for the late component (p = 0.025). No statistical differences have been found between T0 and T1 HFO duration (p > 0.05). We further evaluated the N20 amplitude from the onset to the N20 peak to avoid possible interpretational bias. No statistical differences have been found between T0 and T1 (p = 0.437). Conclusion Our clinical hypothesis, supported by preliminary data, is that vibrotactile afference delivered by the device could work by interfering with the somatosensory processing, rather than by peripheral effects.